Wild Walls. - Coelewij, Leontine; Fuchs, Rudi H.; Gordon, David; Hermans, Benoît; Seward, Keith; Starr, Georgina; Vandamme, F.; van Nieuwenhuyzen, Martijn (Amsterdam : Stedelijk Museum Amsterdam, 1995)
Althoff, Kai ; Collishaw, Mat ; Currin, John ; Decock, Anne ; Gordon, Douglas ; Hermans, Benoît ; Hume, Gary ; Mik, Aernout ; Multiple Autorenschaft Lienz ; Rist, Pipilotti ; Schnitger, Lara ; Schu, ManfreDu ; Starr, Georgina ; Wilson, Jane & Louise
biografie
Wild Walls, Stedelijk Museum Amsterdam, 15 september - 29 oktober 1995
Nederlands & Engels
boek